Myths & Legends of the Celtic Race - Rolleston, T. W. (Thomas William), 1857-1920 (Salt Lake City, UT : Project Gutenberg, 2010)
"Myths & Legends of the Celtic Race" by T. W. Rolleston is a historical account written in the early 20th century. This work delves into the rich heritage, traditions, and influences of the Celtic people, tracing their historical significance across Europe, particularly in the British Isles, and examining how their mythology and folklore contribute to the modern understanding of their culture. The book serves as a celebration of the Celtic race's impact on literature, art, and history, presenting the argument that their influence has been obscured over the ages. The opening of the book presents a powerful preface that emphasizes the enduring legacy of the past and the importance of recognizing the contributions of the Celtic race to contemporary society. It argues against the common use of the term "Anglo-Saxon" to describe the British people, positing instead that "Anglo-Celtic" better captures the unique blend of cultural influences. The preface sets the tone for the subsequent chapters, promising an exploration of Celtic myths, religion, and their historical narrative. Additionally, it critiques the simplification of the Celtic identity and foreshadows discussions that will uncover the complexities and richness of Celtic history and mythology. (This is an automatically generated summary.)
Release date is 2010-10-17
Keywords: Celts -- Religion; Mythology, Celtic